2019
DOI: 10.2174/1573397114666180425111901
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Manifestations of Sarcoidosis: A Review Article

Abstract: Sarcoidosis is a multisystem inflammatory disease with an etiology that is not clearly understood. Amongst the different organs that may be affected, the lungs are the most common. Musculoskeletal manifestations of the disease are uncommon. They include arthropathy, bone lesions, or myopathy, all of which may occur as initial symptoms or develop during the course of the disease. Articular involvement my present as arthralgia or arthritis. Skeletal complications usually develop in the chronic state of the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Due to lack of specific description of periarthritis in the clinical notes, we are unable to report the frequency of periarthritis in this cohort. Prior studies have shown a female predominance for Lofgren syndrome, a higher prevalence of Lofgren syndrome in Caucasians while showing a low prevalence in Japan and India 3,7,14,15,17‐20 . We found Lofgren syndrome predominantly affecting the ankle joint (96.3%), which is similar to previous studies (reported between 75%‐90%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Due to lack of specific description of periarthritis in the clinical notes, we are unable to report the frequency of periarthritis in this cohort. Prior studies have shown a female predominance for Lofgren syndrome, a higher prevalence of Lofgren syndrome in Caucasians while showing a low prevalence in Japan and India 3,7,14,15,17‐20 . We found Lofgren syndrome predominantly affecting the ankle joint (96.3%), which is similar to previous studies (reported between 75%‐90%).…”
Section: Discussionsupporting
confidence: 90%
“…We also found a higher prevalence of sacral and femoral involvement (40% each). In our cohort we did not capture any patients with involvement of the small bones of hand, but this has been reported in other studies as a common site of involvement 5,9‐11,19,23‐26 . Similar to our study, treatment has involved use of steroids, methotrexate and hydroxychloroquine, 11 with prednisone and methotrexate appearing most effective in our cohort.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Pulmonary and extra-pulmonary involvements (skin, bone, bone marrow, SNC, myocardium …) are simultaneously evaluated, with time and cost-saving implications [ 149 , 157 , 166 , 167 ]. Bone biopsy is not necessary in patients with proven disease and typical bone involvement based on [ 18 F]FDG PET/CT or MRI [ 168 ]. [ 18 F]FDG PET/CT may be superior to CT or MRI for detecting bone and bone marrow sarcoidosis [ 169 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, sarcoidosis can cause a wide variety of musculoskeletal complaints affecting the bones, joints, or muscles with joint involvement manifested as acute or chronic arthritis [109, 137]. Curiously, in Japanese individuals, enlargement of spleen has also reported in a considerable number of patients with sarcoidosis, which was linked to a specific genetic background [129].…”
Section: Main Textmentioning
confidence: 99%